André Gorz: wage labour, free time and ecological reconstruction. Issue 2 (3rd May 2016) - Gollain, Francoise
ABSTRACT: André Gorz (1923–2007), a leading theorist of the French left, argued that the ecological reconstruction of society required a transformation of its political culture and economic basis. This case is made in his influential 1978 volume Ecology as Politics and developed in subsequent books and articles discussing the link between alienated labour, technocratic ideology and environmental destruction. His work's critical and emancipatory vision reflects the synthesis of Marxist, existentialist and ecological elements. Gorz advocated a reduction in heteronomous labour and a corresponding expansion in the sphere of autonomy, supported by the distribution of society's wealth among all its members in the form of a guaranteed social income. The present article (originally published in 2007 in Entropia, the theoretical and political journal of the French degrowth movement) offers a detailed account of Gorz's work, highlighting its pertinence to ecological politics. It concludes by summarising his last writings, in which he argued that the recent crises of capitalism showed that it was more than ever necessary to realise the productive powers of twenty-first-century technology not by expanding still further the manufacture and sale of commodities, but by creating a social and economic order in which goods and work would be provided for the common good.